Spinal Cord Paracoccidioidomycosis: Case Report - Hack, Ivan; Brandalise, Alcides, Junior; Furlanetto, Luciano Marques; Lipp, Fernando Bergel; Furian, Roque; Nácul, Cyrio Luiz; Rota, Eduardo Werlang; Muller, Rodrigo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by fungi Paracoccidioides brasiliensis and Paracoccidiodes Lutzii. Its distribution is limited to subtropical regions of Central and South America, where it is endemic, and Brazil accounts for ∼ 80% of the reported cases. Even in endemic zones, its incidence is low, ranging from 3 to 4 new cases per million to 1 to 3 new cases per 100 thousand inhabitants per year. Granulomas in the spinal cord are rare, and they account for 0,6% of all cases of systemic PCM. The authors report a case of a woman with crural paraparesis caused by dorsal spinal cord PCM granulomasin T7-T8 and T8-T9, with no evidence of systemic disease. The patient was submitted to microsurgery, with total excision of the lesions, and is experiencing positive neurological recovery. Though rare, PCM intramedullary granulomas must be considered in differential diagnosis of the tumoral expansive process of the spinal cord, especially in patients coming from endemic rural zones.
Keywords: paracoccidioidomycosis; spinal cord; granuloma